2016
DOI: 10.1016/j.expthermflusci.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of pre-set counter-rotating streamwise vortices in wavy channel

Abstract: Development of counter-rotating streamwise vortices in a rectangular channel with onesided wavy surface has been experimentally quantified using hot-wire anemometry. The wavy surface has fixed amplitude of 3.75 mm. The counter-rotating vortices are pre-set by means of a sawtooth pattern cut at the leading edge of the wavy surface. Variations of the central streamwise velocity U c with a channel gap H = 35 mm and 50 mm (corresponding to a Reynolds number from 1600 to 4400) change the instability of the flow whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…When amplitude of the wavy surface is doubled from the amplitude used in the earlier study by Budiman et al (2015), it is found that the streamwise counter-rotating vortices have a notably different appearance, regardless of the Reynolds number. Budiman et al (2015) presented streamwise counter-rotating vortices with a relatively long mushroom stem and small mushroom hat. In contrast, due to larger amplitude used in this study, the mushroom hat was much bigger, as depicted in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When amplitude of the wavy surface is doubled from the amplitude used in the earlier study by Budiman et al (2015), it is found that the streamwise counter-rotating vortices have a notably different appearance, regardless of the Reynolds number. Budiman et al (2015) presented streamwise counter-rotating vortices with a relatively long mushroom stem and small mushroom hat. In contrast, due to larger amplitude used in this study, the mushroom hat was much bigger, as depicted in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Smoke-wire flow visualization technique was used in this study, similar to the previous study by Budiman et al (2015). Paraffin oil is selected as smoke-generating fluid.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…This current study aims to characterize the induced counter-rotating streamwise vortices which evolve in channel flow with one-sided corrugated wall. Recently, Budiman et al (2016) discussed the development of such vortices by means of hot-wire anemometry. However the report is only limited to the spanwise y − z plane.…”
Section: Introductionmentioning
confidence: 99%
“…However the report is only limited to the spanwise y − z plane. This paper is intended to complement that report by focusing on the streamwise x−y and x−z planes, together with discussions on mixing properties that have not been covered by Budiman et al (2016).…”
Section: Introductionmentioning
confidence: 99%